Glycosylation gene expression profiles enable prognosis prediction for colorectal cancer - Rui Li; Sha He; Ting Qin; Yanyan Ma; Kunyao Xu; Shan Liu; Wei Zhan (Scientific Reports)
Abstract This study developed a prognostic model for patients with colon adenocarcinoma (COAD) based on glycosylation-associated genes. By analyzing TCGA-COAD data, 110 key genes were identified, and a prognostic model incorporating five glycosylation-related genes was constructed. The model exhibits good predictive performance and is significantly associated with clinical features such as age, N stage, M stage, and lymph node count. The prognostic genes are involved in various biological processes and pathways, influence T cell differentiation, and may contribute to CRC development. High-risk patients show a higher degree of immune cell infiltration. This model aids in the early diagnosis, prognosis assessment, and treatment planning for CRC, and offers a direction for further research.